alpha-Difluoromethylornithine, an irreversible inhibitor of ornithine decarboxylase, inhibits tumor promoter-induced polyamine accumulation and carcinogenesis in mouse skin. - Weeks, C E (1982)
The role of ornithine decarboxylase (OrnDCase, EC 4.1.1.17) and of the polyamines [putrescine (Put), spermidine (Spd), and spermine (Spm)] in mouse skin tumor promotion was investigated by the use of alpha-difluoromethylornithine (CHF2-Orn), an enzyme-activated irreversible inhibitor of OrnDCase. 12-O-Tetradecanoylphorbol 13-acetate (TPA), mezerein, and ethyl phenylpropiolate (EPP) were employed as complete, stage II specific, and nonpromoting agents, respectively. TPA and mezerein, but not EPP, provided for a dose-dependent increase in tissue Put accumulation. The Put level in papillomas developed by TPA (2 micrograms) treatment was approximately equal to 15-fold higher than that of the surrounding skin tissue; Spd accumulation was 2- to 3-fold greater in the papillomas. Put administered (intraperitoneally) with TPA greatly enhanced papilloma yield. CHF2-Orn, given orally or intraperitoneally, abolished the TPA-induced OrnDCase activity and Put accumulation in mouse epidermis. The reduction of polyamine accumulation by CHF2-Orn was directly proportional to reduction of tumor size. CHF2-Orn administered in a two-stage (TPA-mezerein) promotion protocol [Slaga, T. J., Fischer, S. M., Nelson, K. G. & Gleason, G. L. (1980) Proc. Natl. Acad. Sci. USA 77, 3659-3663; Slaga, T. J., Klein-Szanto, A. J. P., Fischer, S. M., Weeks, C. E., Nelson, K. & Major, S. (1980) Proc. Natl. Acad. Sci. USA 77, 2251-2254] reduced tumor size, inhibited by 65-70% the number of papillomas per mouse, and decreased by 40% the percentage of mice with tumors when given with the stage II agent mezerein. CHF2-Orn provided considerably less effect on tumorigenesis when administered with the TPA portion of the protocol, and CHF2-Orn did not inhibit the induction of dark basal keratinocytes by TPA. Based on our results with CHF2-Orn, we suggest that regulation of polyamine biosynthesis, particularly Put, is a critical factor in stage II promotion.